Gut bacterial communities and their assembly processing in Cnaphalocrocis medinalis from different geographic sources - Yang, Yajun; Liu, Xiaogai; Guo, Jiawen; Xu, Hongxing; Liu, Yinghong; Lu, Zhongxian (Frontiers in Microbiology, 2022)
The insect gut harbors numerous microorganisms that may have functions in development and reproduction, digestion, immunity and protection, and detoxification. Recently, the influence factors on gut microbiota were evaluated in the rice leaffolder Cnaphalocrocis medinalis, a widespread insect pest in paddy fields. However, the relationship between gut microbiota composition and geography is poorly understood in C. medinalis. To reveal the patterns of C. medinalis gut bacterial communities across geographic sources and the ecological processes driving the patterns, C. medinalis were sampled from six geographic sources in China, Thailand and Vietnam in 2016, followed by gut bacterial 16S ribosomal RNA gene sequencing. A total of 22 bacterial phyla, 56 classes, 84 orders, 138 families, 228genera, and 299 species were generated in C. medinalis from six geographic sources. All alpha diversity indices differed among the samples from different geographic sources. Analysis of similarity (ANOSIM) and permutational multivariate analysis of variance (PERMANOVA) both revealed significant differences in the gut microbiota of C. medinalis from six geographic sources. A total of 94 different taxa were screened as indicators for the gut microbiota of C. medinalis from six geographic sources by linear discriminant analysis effect size (LEfSe). The gene ontology (GO) pathways of the gut microbiota in C. medinalis differed among geographic sources. In total, the bacterial communities within geographic sources were mainly determined by stochastic processes, and those between geographic sources were mainly determined by deterministic processes. This study elucidates that geography plays a crucial role in shaping the gut microbiota of C. medinalis. Thus, it enriches our knowledge of gut bacteria in C. medinalis and sheds light on the mechanisms underlying C. medinalis gut microbial shifts across geography.